One-Year Healthcare Utilization for Patients That Received Endovascular Treatment Compared With Control. Issue 7 (July 2019) - Kamal, Noreen; Rogers, Edwin; Stang, Jillian; Mann, Balraj; Butcher, Kenneth S.; Rempel, Jeremy; Jeerakathil, Thomas; Shuaib, Ashfaq; Goyal, Mayank; Menon, Bijoy K.; Demchuk, Andrew M.; Hill, Michael D.
Abstract : Background and Purpose—: Endovascular therapy has been shown to be highly efficacious based on 90-day modified Rankin Scale score. We examined actual daily healthcare utilization from stroke onset to 1 year afterward from the ESCAPE trial (Endovascular Treatment for Small Core and Anterior Circulation Proximal Occlusion With Emphasis on Minimizing CT to Recanalization Time) and registry data. Methods—: We examined patients from Alberta, Canada, that was enrolled into the ESCAPE trial and the Quality Improvement and Clinical Research registry in the 2016/2017 fiscal year. Through data linkages to several administrative data sets, the daily location of each patient was assessed in various healthcare settings. Results—: A total of 286 patients were analyzed, 52 patients were in the treatment arm, and 47 patients were in the control arm of the ESCAPE trial while 187 patients received endovascular therapy as usual care (2016/2017 fiscal year). The odds of a patient being out of a healthcare setting over 1 year was significantly higher when they received endovascular therapy: 3.46 (1.68–7.30) in ESCAPE trial patients and 2.00 (1.08–3.75) in the Quality Improvement And Clinical Research patients. Conclusions—: Endovascular therapy significantly reduces healthcare utilization up to 1 year after a stroke. Abstract : Supplemental Digital Content is available in the text.